Strategi Komunikasi Bye Bye Plastic Bags dalam Mengedukasi Masyarakat untuk Mengurangi Penggunaan Kantong Plastik - -, Alexandra; Alit Suryawati, I Gusti Agung; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium, 2021)
Since the issuance of the Bali Governor Regulation No. 97 of 2018 concerning the Limitation of Single-Use Plastics, Bye Bye Plastic Bags (BBPB) is moved to educate the public on the importance of reducing the use of plastic bags starting from the younger generation. The purpose of this study was to examine the communication strategy with the object in this study, namely Bye Bye Plastic Bags. This type of research is descriptive qualitative using data collection techniques such as interviews, observation, and document study. Results is that BBPB educates its audiences by conducting workshops, talk shows, presentations, booklets, as well as work programs such as mountain mama, beach clean up, and river booms. BBPB makes use of both print and social media to convey messages to its target audience. Keywords: Plastic Bags, Bye Bye Plastic Bags, Education, Communication Strategy